Tìm x : 2x - 12 - x =0
( x - 7) . ( 2x - 8) = 0
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, 12 - (2\(x^2\) - 3) = 7
2\(x^2\) - 3 = 12 - 7
2\(x^2\) - 3 = 5
2\(x^2\) = 8
\(x^2\) = 4
\(\left[{}\begin{matrix}x=-2\\x=2\end{matrix}\right.\)
7)(16-8x)(2-6x)=0
=> 16 - 8x = 0 hoặc 2 - 6x = 0
=> 16 = 8x hoặc 2 = 6x
=> x = 2 hoặc x = 1/3
8) (x+4)(6x-12)=0
=> x + 4 = 0 hoặc 6x - 12 = 0
=> x = -4 hoặc x = 2
9) (11-33x)(x+11)=0
=> 11 - 33x = 0 hoặc x + 11 = 0
=> x = 1/3 hoặc x = -11
10) (x-1/4)(x+5/6)=0
=> x - 1/4 = 0 hoặc x + 5/6 = 0
=> x = 1/4 hoặc x = -5/6
11) (7/8-2x)(3x+1/3)=0
=> 7/8 - 2x = 0 hoặc 3x + 1/3 = 0
=> 2x = 7/8 hoặc 3x = -1/3
=> x = 7/16 hoặc x = -1/9
12)3x-2x^2=0
=> x(3 - 2x) = 0
=> x = 0 hoặc 3 - 2x = 0
=> x = 0 hoặc x = 3/2
\(a,\left(16-8x\right)\left(2-6x\right)=0\)
\(\hept{\begin{cases}16-8x=0\\2-6x=0\end{cases}\Rightarrow\hept{\begin{cases}x=2\\x=\frac{1}{3}\end{cases}}}\)
\(b,\left(x+4\right)\left(6x-12\right)=0\)
\(\hept{\begin{cases}x+4=0\\6x-12=0\end{cases}\Rightarrow\hept{\begin{cases}x=-4\\x=2\end{cases}}}\)
\(c,\left(11-33x\right)\left(x+11\right)=0\)
\(\hept{\begin{cases}11-33x=0\\x+11=0\end{cases}\Rightarrow\hept{\begin{cases}x=\frac{1}{3}\\x=-11\end{cases}}}\)
\(d,\left(x-\frac{1}{4}\right)\left(x+\frac{5}{6}\right)=0\)
\(\hept{\begin{cases}x-\frac{1}{4}=0\\x+\frac{5}{6}=0\end{cases}\Rightarrow\hept{\begin{cases}x=\frac{1}{4}\\x=-\frac{5}{6}\end{cases}}}\)
\(e,\left(\frac{7}{8}-2x\right)\left(3x+\frac{1}{3}\right)=0\)
\(\hept{\begin{cases}\frac{7}{x}-2x=0\\3x+\frac{1}{3}=0\end{cases}\Rightarrow\hept{\begin{cases}x=\frac{7}{4}\\x=-\frac{1}{9}\end{cases}}}\)
\(f,3x-2x^2=0\)
\(x\left(3-2x\right)=0\)
\(\hept{\begin{cases}x=0\\3-2x=0\end{cases}\Rightarrow\hept{\begin{cases}x=0\\x=\frac{3}{2}\end{cases}}}\)
2x+69.2=69.4
2x+138=276
2x = 276-138
2x = 138
x = 138:2
x = 69
2x-12-x = 0
<=> 2x-x-12 =0
(2x-x)-12=0
=> x-12=0
x = 0+12
x =12
(x-7)(2x-8)=0
\(\Rightarrow\hept{\begin{cases}x-7=0\\2x-8=0\end{cases}}\Rightarrow\hept{\begin{cases}x=7\\x=4\end{cases}}\)
Vậy ...
a, 2X+69.2=69.4
2X+138=276
2X=276-138=138
X=138:2=69
b,2X-12-x=0
2X-X=12-0
x=12
mik chi biet vay thoi con cau cuoi mik chiu
b: \(\Leftrightarrow x^4-4x^2+2x^2-8=0\)
\(\Leftrightarrow x+2=0\)
hay x=-2
\(2x-12-x=0\)
\(\Leftrightarrow2x-x=12\Leftrightarrow x=12\)
\(\left(x-7\right)\left(2x-8\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x-7=0\\2x-8=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=7\\2x=8\end{cases}\Leftrightarrow\orbr{\begin{cases}x=7\\x=4\end{cases}}}\)